2005
DOI: 10.1152/jn.01164.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Representation of Temperature in Mosquito Warm and Cold Cells

Abstract: A pair of antagonistic thermoreceptive cells is associated with each of two peg-in-pit sensilla located on the antennal tip of Aedes aegypti. One, the warm cell, responds to rapid warming with a sudden increase in the rate of discharge. The other, a cold cell, responds to rapid cooling with a sudden increase in the discharge rate. When temperature changes are provided by oscillating changes in the convective heat contained in the stimulating air stream, the oscillating discharge rates of both cell types are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 16 publications
2
52
0
Order By: Relevance
“…The thermal effect may lag behind the IR oscillation, and the lag may be longer during the falling than the rising phase of radiation power. Such a phase shift has not been observed in the tick (Gingl and Tichy 2001) or mosquito (Gingl et al 2005). It may well reflect differences in the mechanisms underlying IR sensitivity of the bug's warm cells.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The thermal effect may lag behind the IR oscillation, and the lag may be longer during the falling than the rising phase of radiation power. Such a phase shift has not been observed in the tick (Gingl and Tichy 2001) or mosquito (Gingl et al 2005). It may well reflect differences in the mechanisms underlying IR sensitivity of the bug's warm cells.…”
Section: Discussionmentioning
confidence: 91%
“…Each sensory organ houses a cell pair consisting of a warm cell and a cold cell responding antagonistically to changes in air T. As in other arthropods such as the tick Ixodes ricinus (Gingl and Tichy 2001) and the mosquito Aedes aegypti (Gingl et al 2005), the two types of warm cells of the bug's antenna are excited not only by increasing air T, but also by increasing IR power. However, well-designed behavioral experiments have convincingly shown that bloodsucking bugs are able to discriminate between T and IR stimuli (Lazzari and Núñez 1989;Schmitz et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By means of electrophysiological recordings, however, we have shown that both types of sense organs contain a pair of antagonistically responding warm and cold cells. As is the case with the thermoreceptive cells of other insects such as mosquitoes, cockroaches, migratory locusts, and also ticks (Gingl et al 2005;Gingl and Tichy 2001), the warm and cold cells of the peg-inpit sensillum and the tapered hair respond to both T and IR stimuli.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to the high sensitivity to changes in air temperature (T), Davis and Sokolove (1975) reported that warm and cold cells of mosquitoes did not respond to infrared radiation (IR). A later study, however, provided evidence that the discharge rates of the mosquito's warm and cold cells are modulated by oscillating changes in temperature and IR (Gingl et al 2005).…”
mentioning
confidence: 96%